Pembuatan Pestisida Nabati Pada Kelompok Tani Wanita Sejahtera di Desa Sikapat - Ratna Dwi Hirma Windriyati; Larin Tikafebianti; Gita Anggraeni (Universitas Lancang Kuning, 2020)
The Women Farmer Group Sejahtera mostly housewives or decorative plant farmer in Sikapat villages, Sumbang district, Banyumas regency. Its located in northern city of Purwokerto, within 15,2 km from UNU Purwokerto. Its location in highland (800 masl) has good potential for horticultural and ornamentalplant cultivation. One obstacle of farmer group is presence of pest and pathogen. Control usually done by farmer with spraying sinthetic pesticides. This PKM provides another alternative, used botanical pesticides that more environmentally friendly, through training make botanical pesticides. The methode used was counseling, training and application. The result of PKM was an increase knowledge and skills about the benefits and ways of making botanical pesticides from plants around the house. Botanical pesticides can reduce production costs and potentially as a home industry.